Are BBA students ready for social entrepreneurship? an application of theory of planned behavior - Kulal, Namaraj (Journal of Emerging Management Studies, 2023)
Purpose – The aim of the study was to investigate the behavioral intentions of BBA students regarding their engagement in social entrepreneurship.Design/methodology/approach – To attain this purpose, a cross-sectional survey research design was used, and data were gathered from a sample of 205 respondents. Hypotheses were tested through the application of Ordinary Least Square (OLS) regression analysis.Finding – This paper found a significant positive effect of subjective norms and perceived behavioral control on behavioral intention of social entrepreneurship. However, this paper found no significant influence of attitude towards social entrepreneurship on behavioral intention of social entrepreneurship.Practical Implications – In light of these findings, this paper provides both theoretical and practical implications for further understanding and fostering social entrepreneurship among BBA students.